Baseline Characteristics and Disease Phenotype in Inflammatory Bowel Disease. Issue 1 (January 2016) - Müller, Katalin E.; Lakatos, Peter L.; Kovacs, Judit B.; Arato, Andras; Varkonyi, Agnes; Nemes, Eva; Tarnok, Andras; Toth, Gergely; Papp, Maria; Solyom, Eniko; Horvath, Agnes; Guthy, Ildiko; et al.
ABSTRACT: Objectives: Predicting short-term relapses and long-term prognosis is of utmost importance in paediatric inflammatory bowel disease (IBD). Our aim was to investigate the short-term disease outcome and medication during the first year in a paediatric incident cohort from Hungary. In addition, association laboratory markers and disease activity indices with short-term disease outcome and medication were analysed. Methods: From January 1, 2008 to December 31, 2010, demographic data and clinical characteristics of newly diagnosed paediatric patients with IBD <18 years of age were prospectively recorded. Results: A total of 420 patients were identified (Crohn disease [CD] 266 and ulcerative colitis [UC] 124). Initially, 48% (124/256) of the patients with CD had moderate-to-severe disease (Pediatric Crohn's Disease Activity Index [PCDAI] >31), and this rate decreased to 2.1% at 1-year follow-up. Proportion of patients with UC with moderate-to-severe disease (Pediatric Ulcerative Colitis Activity Index >35) at diagnosis declined from 57.5% (69/120) to 6.8% at 1-year follow-up. Terminal ileal involvement correlated with higher initial C-reactive protein (CRP) ( P = 0.021) and initial PCDAI ( P = 0.026). In UC, elevated CRP ( P = 0.002) was associated with disease extension. CRP and PCDAI at diagnosis were associated with the need for immunomodulators at 1 year in children with CD. Initial CRP was also associated with the need for immunomodulators in patients with UC at 1-year follow-up. Conclusions: At diagnosis, half of the patients with IBD had moderate-to-severe disease, and this rate decreased to <10% after 1 year. Initial CRP and PCDAI were related to the need for aggressive therapy in CD. Abstract : Supplemental Digital Content is available in the text